A Survey on the Relationship Between Knowledge Management with Job Performance and Open Innovation in Employees of West Regional Electric Company - faramarz soheili; saleh rahimi; Fatemeh Aivatvandy pour (تحقیقات کتابداری و اطلاع‌رسانی دانشگاهی, 2019)
Purpose: The purpose of this study was to investigate the relationship between knowledge management and job performance and open innovation among West Regional Electric Company employees.Method: The research method was descriptive correlational and the statistical. Using simple random sampling 140 people were selected as sample. Three questionnaires were used for collecting data. For the validity of the questionnaires, management experts have been used. The reliability of the questionnaires was also based on Cronbach's alpha coefficient. The research data were analyzed using independent T-analysis and multiple regression analysis. Findings: The findings indicate that: 1. Knowledge management has a positive and significant effect on job performance and its components (behavioral behavior and underlying performance). 2. Knowledge management has a positive and significant impact on open innovation and its components (exploration and exploitation). 3- There is a difference between the knowledge management with the job performance and the open innovation by gender.Results: The results of research may help managers in designing knowledge management programs to achieve better business performance, more open innovation and a more sustainable competitive advantage.